2019
DOI: 10.1111/ina.12616
|View full text |Cite
|
Sign up to set email alerts
|

Radon and moisture impacts from interventions integrated with housing energy retrofits

Abstract: Energy retrofits can reduce air exchange, raising the concern of whether indoor radon and moisture levels could increase. This pre/post‐intervention study explored whether simple radon interventions implemented in conjunction with energy retrofits can prevent increases in radon and moisture levels. Treatment homes (n = 98) were matched with control (no energy retrofits or radon intervention) homes (n = 12). Control homes were matched by geographic location and foundation type. t‐tests were used to determine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Radon 222 Rn is an odorless and colorless radioactive gas [1,2]. It is formed from the decay of 226 Ra, which is a member of the 238 U decay chain [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radon 222 Rn is an odorless and colorless radioactive gas [1,2]. It is formed from the decay of 226 Ra, which is a member of the 238 U decay chain [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Aquilina and Fenech (2019) studied the influence of various meteorological parameters on indoor radon levels in four different locations in the Maltese Islands and found that indoor radon levels mostly depended on the outdoor relative humidity and wind speed [24]. The majority of the studies on indoor radon levels and their seasonal variations were performed in dwellings [1,10,13,23,25]. However, some studies were performed on indoor radon levels in workplaces, such as offices and industrial buildings [26][27][28][29], hospitals [26,30,31], and schools [26,32].…”
Section: Introductionmentioning
confidence: 99%
“…As it will be discussed further, type of flooring could be a reason of this large indoor radon variability. An active radon mitigation system implies covering of porous floors with appropriate covers or materials which prevent radon leakage (Francisco et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies concluded that materials like granite and other stones used in older houses may increase radon levels, while over-pressurized ventilation systems may decrease radon levels (Collignan et al 2016). In crawl spaces, ventilation can also decrease radon when it is emitted by construction materials, rather than by the soil or foundations (Francisco et al 2020).…”
Section: Radonmentioning
confidence: 99%